2004
DOI: 10.1111/j.1742-7924.2004.00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening of domestic violence against women in the perinatal setting: A systematic review

Abstract: Aim:  To review published studies focusing on the screening of domestic violence (DV) against women, in particular, the instruments, the screening methods and the interventions used to help abused women after screening. Based on the results of the review, the suitability of introducing routine screening for DV in the perinatal setting in Japan would be assessed. Methods:  National Guideline Clearinghouse database, HSTAT, PubMed, CINAHL, the Cochrane Library and the Ichushi‐Web were all used to searched from wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…Hindin (2006) found that there was need to enter into a trusting relationship with the women before screening. The need for appropriate and culturally relevant ways of asking the screening questions has been reported in Japan (Kataoka et al 2004) and in the USA (Hindin 2006). The midwives in our study raised difficulties asking questions in their vernacular, which may suggest that any screening tool designed should be culturally relevant.…”
Section: Discussionmentioning
confidence: 73%
“…Hindin (2006) found that there was need to enter into a trusting relationship with the women before screening. The need for appropriate and culturally relevant ways of asking the screening questions has been reported in Japan (Kataoka et al 2004) and in the USA (Hindin 2006). The midwives in our study raised difficulties asking questions in their vernacular, which may suggest that any screening tool designed should be culturally relevant.…”
Section: Discussionmentioning
confidence: 73%
“…Consequently, multiple programs within health care settings have been developed to identify women experiencing IPV; however, substantial variation in program content and effectiveness has created challenges in drawing conclusions [79]. Additionally, controversy exists regarding the clinical merits of universal screening [713].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, controversy exists regarding the clinical merits of universal screening [713]. Those who support universal screening in health care settings argue that effective screening tools are available [9], screening increases IPV detection rates [14, 15], and the majority of women view screening as acceptable provided that it is conducted in private, sensitive, and non-judgmental manner [16, 17]. Those who do not support universal screening argue that there is insufficient evidence to support implementation [7, 11] and that potential adverse outcomes from such programs are unknown [8].…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been a number of international reviews establishing the effectiveness of training in identifying victims of domestic abuse (Wathen and MacMillan, 2003;Ramsay et al, 2002;Kataoka, et al, 2004;U.S. Preventive Service Task Force, 2004;Feder et al, 2009).…”
Section: Introductionmentioning
confidence: 99%